Investigation of a coaxial Stirling-type pulse tube cryocooler with the cooling capacity of 600 W at 77 K. (April 2019) - Li, Jiaqi; Tan, Jun; Zha, Rui; Zhang, Tao; Zhao, Bangjian; Zhao, Yongjiang; Dang, Haizheng
Abstract: This paper conducts the investigation of a coaxial Stirling-type pulse tube cryocooler (SPTC) with the cooling capacity of 600 W at 77 K, in which a two-dimensional CFD model is established and the effects of the flow are studied. With the aimed high cooling capacity, the flow straighteners at both inlet and outlet of the pulse tube become crucial to ensure the cooling performance by minimizing the turbulence flows in it. The interaction of the pulse tube cold finger and the linear compressor is investigated in view of that the match between them plays an important role in improving the cooling performance. In the experiment, the SPTC has a cooling capacity of 580 W at 77 K with the relative Carnot efficiency of 12%.